Pliocene and pleistocene volcanic interaction with cordilleran ice sheets, damming of the Yukon River and vertebrate palaeontology, Fort Selkirk volcanic group, west-central Yukon, Canada - Jackson, L.E.; Nelson, F.E.; Huscroft, C.A.; Villeneuve, M.; Barendregt, René W.; Storer, J.E.; Ward, B.C. (Elsevier, 2012)
Accepted author manuscript Neogene volcanism in the Fort Selkirk area began with eruptions in the Wolverine Creek basin ca. 4.3 Ma and persisted to ca. 3.0 Ma filling the ancestral Yukon River valley with at least 40 m of lava flows. Activity at the Ne Ch’e Ddhäwa eruptive center overlapped with the last stages of the Wolverine Creek eruptive centers. Hyaloclastic tuff was erupted between ca. 3.21 and 3.05 Ma. This eruption caused or was coincident with damming of Yukon River. The first demonstrable incursion of a Cordilleran ice sheet into the Fort Selkirk area was coincident with a second eruption of the Ne Ch’e Ddhäwa eruptive center ca. 2.1 Ma. The Ne Ch’e Ddhäwa subglacial mound was erupted beneath at least 300 m of glacial ice (Ne Ch’e Ddhäwa Glaciation). The Eruption of the Fort Selkirk center occurred between the last eruption of Ne Ch’e Ddhäwa and Fort Selkirk Glaciation (ca. 2.1e1.5 Ma). Till and outwash from Fort Selkirk Glaciation are conformably overlain by nonglacial sediments that contain the Fort Selkirk tephra (fission track dated at ca. 1.5 Ma). These nonglacial sediments also preserve a short magnetic reversal (reversed to normal) identified as the Gilsá polarity excursion. Temporal control and sedimentology constrain Fort Selkirk Glaciation and the Fort Selkirk Local Fauna to marine isotope stage 54. Rapid and extensive eruption of the Pelly eruptive center filled the Yukon River valley with 70 m of lava which buried these glacial and nonglacial sediments and dammed Yukon River. Local striations and erratic pebbles occur on the last of these lava flows. They document a subsequent incursion of glacial ice during the last 500 ka of the Matuyama Chron (Forks Glaciation). The last major eruption of mafic lava occurred in the middle Pleistocene west of (early Holocene) Volcano Mountain in basin of Black Creek: lava flowed down the valley presently occupied by Black Creek and dammed Yukon River in the area of the Black Creek confluence. This eruption predated the middle Pleistocene Reid ...